PEMBUATAN MESIN PERAJANG KETELA SERBA GUNA UNTUK INDUSTRI PATILO DAN CERIPING KETELA SKALA KECIL - Karyono, Slamet; Wagiran, Wagiran (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
A group  called  SARILA  in Kauman,  Dadapayu,   Semanu,  Gunung kidul,  had  a problem  of low production   quality  and  capacity  in their  busi ness  of making  patilo  and  fried  cassava  chips  because  the  work  of cutting and scraping  the basic  material  for their products,  cassava,  was done manu ally by using  simple  tools that caused  the cassava  to break  when  cut so that the  resulting   chips  were  also  in  broken  conditions   and  the  manual  work caused the workers  to quickly become  exhausted.  Therefore,  the main objec tive of one voucher  program  was to enable the workers  to do their work me chanically  instead  of manually.It had  to be able  to design  and  produce  an easily-operated   cassava processing  machine  with a frame strong  enough  to withstand  vibrations  and do two kinds  of work,  cutting  and scraping  cassava,  easily,  accurately,  and simultaneously.    An  ergonomic   table  also  had  to  be  developed   to  ensure long-lasting   use  of the machine  in the  cassava  processing.   The  machine  at last successfully  produced  is 90 em in length,  60 em in width,  and 90 em in height,  designed  high enough  to enable the operator  to do the work easily in a standing-up  position.  Stainless  steel  plate  material  is applied  on all parts having direct  contact  with the cassava  processing.  The frame of the machine is made of 5-cm rectangular  steel profiles  to ensure  its being  strong  enough to withstand  operation.  An electrical  motor  with  a power  of  Y2  HP and pul ley-and-belt  transmission   aids the operation.   Such  transmission   enables  the cutting  and scraping  parts to operate  simultaneously   at different  speeds. The position  of the cutting tool can be adjusted  for desired  thickness.  Except the frame, all parts of the machine  are designed  according  to a knock-down  sys tem for easy replacement  of broken parts.The  result  of a performance   test  on the  machine  has  shown  that  itcan  be  operated   easily  without  the  operator   becoming   quickly  exhausted. Compared  to what is produced  in the old ways, the product  looks better; it is smoother,  and there  is less cassava  fibers.  The   product  capacity  of the ma chine  is about  50 kg every  50 minutes  from  its cutting  process  and  50 kg every  75 minutes  from  its scraping  process.  During  operation,   there  is no vibration on its frame. It shows that the construction design is strong enough to withstand the vibration of the motor rotation and cassava processing.Keywords: cassava, multipurpose machine, cutting and scraping